Invasive cervical resorption of central incisor during orthodontic treatment - Gabriela Meyge de Brito; Paulo Sergio Flores Campos; Ana Carolina Ramos Mariz; Diana Simões; Andre Wilson Machado (Dental Press Editora, 2021)
ABSTRACT Introduction: Invasive cervical resorption (ICR) is a relatively rare type of ERR (External Root Resorption), in which a localized resorption begins in the cervical area of the tooth, below the epithelial junction and above the ridge crest. Objective: Describe the clinical case of an 11-year-old boy with no dental trauma history, presenting moderate crowding and ectopic eruption of the maxillary right central incisor. He had been undergoing orthodontic treatment elsewhere, and his family was dissatisfied with the results. Description: A new treatment was indicated, which included rapid maxillary expansion followed by extraction of four premolars. During routine panoramic evaluation, a radiolucid image was detected and a periapical radiograph was requested. At this point, an ICR of the maxillary right central incisor was found. The treatment was cautiously finalized and despite the use of light forces, central incisor was severally compromised by ICR and was therefore extracted. Conclusion: This clinical example discusses the importance of routine radiographs for the early diagnoses of ICR.